Penerapan metode Hirarc K3 mesin gerinda tangan pada industri fabrikasi PT. XYZ - Cahyono, Manggi Dwi; Indiyono, Lalak; Arnold, M Yusuf; Susiati, Devi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
XYZ is one of the industries engaged in the fabrication sector. The workplace is not too large, making the production area full of machines and piles of equipment so that it can cause danger to workers and the company. This study aims to ensure that all workers at PT. XYZ know the procedures for using hand grinders properly and correctly, and comply with all regulations when using work tools. This study uses the HIRARC method to identify the problems experienced. Based on the results of the analysis of the study referring to the occupational safety and health (K3) of hand grinders in the fabrication industry at PT. XYZ shows that there are still many activities that can pose dangerous risks. The solution is to redesign K3 management at PT. XYZ by conducting socialization of the dangers of work accidents and conducting direct and continuous supervision of workers about the importance of using personal protective equipment. So that in the future it is expected to increase productivity in the fabrication industry at PT. XYZ.